Therapeutic implications of Epstein–Barr virus infection for the treatment of nasopharyngeal carcinoma - Hutajulu SH; Kurnianda J; Tan IB; Middeldorp JM (Dove Medical Press, 2014)
Susanna Hilda Hutajulu,1 Johan Kurnianda,1 I Bing Tan,2,3 Jaap M Middeldorp4 1Department of Internal Medicine, Faculty of Medicine Universitas Gadjah Mada/Dr Sardjito General Hospital, Yogyakarta, Indonesia; 2Department of Ear, Nose and Throat, The Netherlands Cancer Institute/Antoni van Leeuwenhoek Hospital, Amsterdam, The Netherlands; 3Department of Ear, Nose and Throat, Faculty of Medicine Universitas Gadjah Mada/Dr Sardjito General Hospital, Yogyakarta, Indonesia; 4Department of Pathology, VU University Medical Center, Amsterdam, The Netherlands Abstract: Nasopharyngeal carcinoma (NPC) is highly endemic in certain regions including the People's Republic of China and Southeast Asia. Its etiology is unique and multifactorial, involving genetic background, epigenetic, and environment factors, including Epstein–Barr virus (EBV) infection. The presence of EBV in all tumor cells, aberrant pattern of antibodies against EBV antigens in patient sera, and elevated viral DNA in patient circulation as well as nasopharyngeal site underline the role of EBV during NPC development. In NPC tumors, EBV expresses latency type II, where three EBV-encoded proteins, Epstein–Barr nuclear antigen 1, latent membrane protein 1 and 2 (LMP1, 2), are expressed along with BamH1-A rightward reading frame 1, Epstein–Barr virus-encoded small nuclear RNAs, and BamH1-A rightward transcripts. Among all encoded proteins, LMP1 plays a central role in the propagation of NPC. Standard treatment of NPC consists of radiotherapy with or without chemotherapy for early stage, concurrent chemoradiotherapy in locally advanced tumors, and palliative systemic chemotherapy in metastatic disease. However, this standard care has limitations, allowing recurrences and disease progression in a certain proportion of cases. Although the pathophysiological link and molecular process of EBV-induced oncogenesis are not fully understood, therapeutic approaches targeting the virus may increase the cure rate and add clinical benefit. The promising results of early phase clinical trials on EBV-specific immunotherapy, epigenetic therapy, and treatment with viral lytic induction offer new options for treating NPC. Keywords: immunotherapy, epigenetic therapy, viral lytic induction therapy